Empathy deficit in male patients with schizophrenia and its relationships with impulsivity and premeditated violence - Gong, Muxin; Yao, Lei; Ge, Xiaodan; Liu, Zhenru; Zhang, Caiyi; Yang, Yujing; Amdanee, Nousayhah; Wang, Chengdong; Zhang, Xiangrong (Frontiers in Psychiatry, 2023)
Objective: To explore the pattern of empathy characteristics in male patients with schizophrenic (SCH) and to examine whether empathy deficit is associated with impulsivity and premeditated violence. Methods: One hundred and fourteen male SCH patients were selected. The general demographic data of the patients were collected, and the subjects were divided into violence group (60 cases) and non-violence group (54 cases) using the Modified Overt Aggression Scale (MOAS). The Chinese version of the Interpersonal Reactivity Index-C (IRI-C) was used to assess empathy, and the Impulsive/Predicted Aggression Scales (IPAS) was used to assess the characteristics of aggression. Results: Among 114 patients, 60 were in the violence group, including 44 patients with impulsive aggression (IA) and 16 patients with premeditated aggression (PM) according to the IPAS scale. The four subfactors of IRI-C (PT, EC, FS and PD) in the violence group were significantly lower than those in the non-violence group. The results of stepwise logistic regression showed that cognitive empathy (Perspective Taking, PT) and impulsive aggression were independent influencing factors for violent behavior in SCH patients. The correlation analysis showed that three factors of empathy (PT, FS and EC) were negatively correlated with impulsive aggression, but not with premeditated aggression. Conclusion: The SCH patients with the violence behavior had more extensive empathy deficits compared with the non-violent SCH patients. Point of view selection and impulsivity are independent influencing factors of violence in SCH patients. Empathy deficiency is an important index to predict impulsive aggression in male patients with schizophrenia.